Expressions of social inequality in the Federal District between 2018 and 2020: The intensification of the "social issue" during the COVID-19 pandemic (Research, Society and Development, 2021)
This article presents preliminary results of the research on the expressions of social inequality in the Federal District (DF) with as reference some of the main socioeconomic data of this reality between the years 2018 and 2020. It is considered that the set of inequalities existing in society is based on the relationship of exploitation of capital over work, governed by the general law of capitalist accumulation, as developed by Marx in chapter 23 of Book 1 of Volume 1 of the work O Capital. The performance of this study is based on the dialectical historical materialism method, using methodological procedures of quantitative-qualitative character. Preliminary studies show the existence of a deep socioeconomic inequality in the Federal District (DF), identifying that the administrative regions that have the lowest income of GDP per capita have the highest unemployment and informal labor rates, a situation that has worsened during the COVID-19 pandemic and ed to the intensification of the expressions of the "social issue", especially with regard to the increase in poverty, unemployment and inequality.